Relationship of cyclosporin and sirolimus blood concentrations regarding the incidence and severity of hyperlipidemia after kidney transplantation - Spinelli,G.A. (2006)
The influence of drug concentrations on the development of persistent posttransplant hyperlipidemia was investigated in 82 patients who received cyclosporin A (CsA) and prednisone plus sirolimus (SRL) (52) or azathioprine (AZA) (30) during the first year after transplantation. Blood levels of CsA and SRL, daily doses of AZA and prednisone, and cholesterol, triglyceride, and glucose concentrations were determined during each visit (pretransplant and 30, 60, 90, 120, 180, and 360 days posttransplant). Persistent hyperlipidemia was defined as one-year average steady-state cholesterol (CavCHOL) or triglyceride (CavTG) concentrations above 240 and 200 mg/dL, respectively. Mean cholesterol and triglyceride concentrations increased after transplantation (P < 0.01) and were higher in patients receiving SRL compared to AZA (P < 0.001). Patients receiving SRL showed a significantly higher number of cholesterol (>229 or >274 mg/dL) and triglyceride (>198 or >282 mg/dL) determinations in the upper interquartile ranges. CsA and SRL interquartile ranges correlated with cholesterol concentrations (P = 0.001) whereas only SRL interquartile ranges correlated with triglyceride concentrations (P < 0.0001). Only pretransplant cholesterol concentration >205 mg/dL was independently associated with development of persistent hypercholesterolemia (CavCHOL >240 mg/dL, relative risk (RR) = 20, CI 3.8-104.6, P = 0.0004) whereas pretransplant triglyceride concentration >150 mg/dL (RR = 7.2, CI 1.6-32.4, P = 0.01) or >211 mg/dL (RR = 19.8, CI 3.6-107.9, P = 0.0006) and use of SRL (RR = 3, CI 1.0-8.8, P = 0.0049) were independently associated with development of persistent hypertriglyceridemia (CavTG >200 mg/dL). Persistent hypercholesterolemia was more frequent among patients with higher pretransplant cholesterol concentrations and was dependent on both CsA and SRL concentrations. Persistent hypertriglyceridemia was more frequent among patients with higher pretransplant triglyceride concentrations and was dependent on SRL concentrations.